Objets instables dans un champ en mouvement, ou comment publier la littérature théâtrale dans les années 2020 - Pauline Guillier (Itinéraires)
“Literature” in general is currently undergoing radical transformations, that are also visible in the way playwrights create and identify themselves. The early 2020s saw the launch of new collections by publishing houses, aiming at blurring the boundaries between theater and literature. These collections respond to various issues within the publishing field, and have an impact on the relations between theater text and literature, on a theoretical level. Furthermore, publishing and artistic practices are also being reinvented through more underground or handcrafted forms (fanzine, self-publishing or ephemera), with the hope of tipping the balance of power governing the relationships between actors of the literary and theatrical fields on a political, economic and aesthetical level. By comparing different publishing gestures, and paying attention to their materiality, I will question how theatrical texts seek their inscription in the literary field, making room for new functions of the text, new editorial and auctorial figures, disrupting their reception.